Multi-column Partitioning for Agent-based CA Model - Tissera, Pablo Cristian (2011)
Computer simulations using Cellular Automata (CA) have been applied with considerable success in different scientific areas, such as chemistry, biochemistry, economy, physics, etc. In this work we use CA in order to specify and implement a simulation model that allows to investigate behavioural dynamics for pedestrians in an emergency evacuation. Two important aspects must be considered when simulating the movement of people: a) estimation of distances from the cells to an exit and b) handling of collisions between individuals. For the first problem, the Dijkstra algorithm was used. In relation to the collisions, we proposed two approaches to solve the movement of people: centralised on a empty cell and distributed in the neighbouring cells. This latter approach leads to the formulation of Agent-based CA Model for pedestrians motion. Finally, in order to accelerate the simulation and take advantage of modern computer architectures, the paper also presents a parallel implementation which is an adaptation of the traditional Ghost Cell Pattern technique. This implementation will be essential when the model complexity increases due to the incorporation of new features. We apply our approaches to several environment configurations achieving important reduction of simulation time.